Primary biphasic synovial sarcoma in a rare anatomical site in an adolescent: a case report - Bhargav, Mithlesh; Thoudam, Valentina; Gupta, Brijnandan; Muraleedharan, Mimna V.; Gupta, Deepika; Gopal, Vaibhav Raj (International Journal of Research in Medical Sciences, 2025)
Synovial sarcoma is a rare malignant soft tissue tumor that predominantly affects adolescents and young adults, commonly arising in the extremities. Head and neck involvement is uncommon, accounting for only 0.7% to 10% of all synovial sarcoma cases. The parapharyngeal space is an especially rare site, representing approximately 0.5% of head and neck tumors. We present the case of an adolescent male with a progressively enlarging mass in the parapharyngeal space. Clinical and radiological evaluation suggested a mesenchymal lesion. Fine-needle aspiration cytology (FNAC), followed by histopathological examination and immunohistochemistry, confirmed the diagnosis of synovial sarcoma. The tumor displayed characteristic biphasic histology and immune profile. The patient underwent surgical resection and was later lost to follow-up. This case highlights the diagnostic challenges posed by mesenchymal tumors in unusual locations such as the parapharyngeal space. A multidisciplinary approach incorporating cytology, histopathology and immunohistochemistry is essential for accurate diagnosis and optimal management. Awareness of such rare presentations is important, especially in adolescents, to avoid misdiagnosis, delayed treatment and recurrence.